Reservoir characteristics and petrophysical controlling factors of the tight sandstone of He-8 member in eastern Yanchuan area, Yan’an gas field - Gao, Yaning; Yin, Shuai; Guo, Haiyang; Jiang, Zhihao (Frontiers in Earth Science, 2025)
The Upper Paleozoic He-8 Member in the southwestern Ordos Basin hosts enormous potential for natural-gas exploration and development, yet the reservoir is highly heterogeneous and still only sparsely drilled. Reservoir quality is the primary control on large-scale accumulation of natural gas. Taking the He-8 Member of the eastern Yanchuan area, Yan’an Gas Field, southwestern Ordos Basin as an example, this study integrates abundant core, grain-size, thin-section, SEM, petrophysical and mercury-injection data to systematically characterize the reservoir and identify the factors that govern its petrophysical properties. The He-8 Member was deposited in a braided-river delta setting. Reservoir lithologies are mainly quartz sandstone, lithic quartz sandstone, high-plasticity lithic sandstone and calcareous-cemented sandstone. Pore types include residual intergranular pores, dissolution pores (feldspar and lithic), intercrystalline pores and micro-fractures; among these, intragranular dissolution pores within volcanic lithics are the most abundant. Net-confined porosity ranges from 0.5% to 15.0% (mean 6.7%), and net-confined permeability from 0.001 × 10-3μm2 to 5.577 × 10-3μm2 (mean 0.053 × 10-3μm2), classifying the interval as an ultra-low-porosity, tight reservoir. Mercury-injection curves and parameters allow the He-8 Member to be subdivided into four reservoir classes, with Type II and Type III curves dominating. Reservoir quality is demonstrably controlled by lithology, diagenetic facies and the diagenetic history. Coarse and medium sandstones exhibit the best properties, followed by fine sandstones; siltstones are poorest. Among diagenetic facies, lithic quartz sandstone displays the highest porosity and permeability, followed by quartz sandstone, lithic sandstone and, lastly, calcareous-cemented sandstone. A diagenetic-stage scheme tailored to each lithology has been established and the diagenetic evolution reconstructed. Rapid early burial subjected the He-8 Member to intense compaction already during the early-diagenetic A1 substage, laying the petrophysical foundation for subsequent tightness. Secondary pores were generated principally by dissolution in the middle-diagenetic A2 substage—the key interval for reservoir-space creation. Entry into the middle-diagenetic B substage saw widespread authigenic precipitation that occluded remaining intergranular and dissolution pores, further tightening the sandstone. These findings provide practical guidance for the exploration and development of natural gas both in the study area and in analogous settings elsewhere.